Imaginando o outro e a nação nas relações internacionais: Commentary Magazine, The New Republic e o intervencionismo dos Estados Unidos na Nicarágua e El Salvador (1977 - 1992) - Moll Neto, Roberto [UNESP] (2015)
This thesis aims to investigate how the discursive narratives about international relations characterize the other and establish ways of imagining the nation as a means of hegemony construction element. More specifically, the analysis focuses on the imaginary of Nicaragua, El Salvador and the United States in the discursive narratives produced by intellectuals in the US journal Commentary Magazine and The New Republic during the period known as the Crisis in Central America between 1977 and 1992. The main hypothesis guiding this research is that these discursive narratives conform negative ways of imagining Central America and, in parallel, positive ways to imagine the United States to justify interventionist policies in the region. Therefore, act as element that builds hegemony of different interventional strategies. To do this analysis, this thesis adopts a methodological theoretical approach rooted in the concepts of civil society, intellectuals, hegemony and imagined community and discursive analysis tools, placing the actors and institutions in the historical processes that develop in United States and Central America